Influence of a supraoptimal fluorine content in drinking water upon development of cephalometric characters of children - Grabowska, Jadwiga; Łuczak, Bogdan (Anthropological Review, 1984)
Material for the present study was collected in a village Błaszki near city of Sieradz where endemic dental changes due to overdose of fluorine occur. 164 boys and 173 girls aged 7 to 10 years were examined by dentists and their anthropometrical characteristics collected. All children ‘ were living in the same socio-economic conditions. The only difference occurred with respect to fluorine content in water they drank (part of the examined children drank pipeline water containing 2.68 mg F per litre, while the other part drank water obtained form farm wells containing 0.05-0.88 mg of fluorine in one litre). As a criterion of division into groups with overdose of fluorine and a „control” group was used presence of spotted enamel on teeth that is the first visible symptom of fluorine overuse. The control group comprised 103 boys and 115 girls, While the overdosed (experimental) group consisted of 61 boys and 58 girls. 10 cephalometric characters were taken into account. During a standard statistical analysis it has been found that children with spotted enamel on their teeth were having smaller head and face dimensions (statistically significant). However, differences in head and face dimensions are smaller than that previously found by the authors for somatometric characters.